Product Innovation in Using Mangosteen Skin in the Making of Batik Steamer - Putri, Utami Hidally; Priatini, Woro; Kusuma, Mandradithya (Gastronomy Tourism Journal, 2019)
The purpose of this research is motivated by the development of mangosteen skin research. Many beneficial ingredients contained in mangosteen peel, such as xanthon which is anti-cancer and anti-oxidant and very beneficial for one's health. The use of mangosteen peel in making steamed batik sponges is as a coloring agent while it is expected to provide benefits when consuming steamed batik sponges. The selection of steamed sponge batik is an appointment of local culture and introduces to tourists. The research method used was an experimental method of adding mangosteen peel to a randomly designed steamed sponge mixture. To test prescription formulations and product quality using organoleptic tests, hedonic tests and consumer acceptance tests. The number of samples used in this study were 15 expert panelists consisting of chefs, academics and practitioners, in addition to general panelists or as many as 100 respondents who were randomly selected. In this study there were three prescription formulations for sample code, namely BKBKM 1 recipe formulation (6% mangosteen skin addition), BKBKM 2 recipe formulation (8% mangosteen skin addition) and BKBKM 3 recipe form (10% mangosteen skin addition). Three recipe formulations were tested on 15 expert panelists who would then produce the most preferred recipe formulations. The recipe from BKBKM 3 is the most preferred recipe formulation. Next, the BKBKM 3 recipe formulation is tested again to respondents or consumers to find out the acceptance test for innovative products. After that, the product is stored at room temperature and in the refrigerator to find out how long the product is safe for consumption.